Formation of Chokan Valikhanov’s linguistic personality and its character as a system - Izbassarova, Elvira I.; Suyerkul, Botagoz M.; Birai, Nergiz; Baigutova, Dinara N.; Salykbayeva, Gulbanu M. (Opción)
The article is devoted to an urgent topic - the study of the human factor in language. The authors of the article set a goal - to describe the main factors that influenced the formation and development of the linguistic personality of the outstanding Kazakh scholar-enlightener Chokan Valikhanov via descriptive research method and discoursive analysis. As a result, the text is a system category in which all the macro-components of the linguistic and textual personality. In conclusion, the anthropological data of the biography of Chokan Valikhanov are the main features of the formation of his linguistic personality.